A numerical simulation study of ash deposition in a circulating fluidized bed during Zhundong lignite combustion. (1st February 2023) - Liang, Yintang; Li, Jianbo; Long, Xiaofei; Lu, Xiaofeng; Zhang, Dongke
Highlights: Ash deposition during ZD CFB combustion simulated by a novel critical viscosity model. Simulation result with a deposit thickness of 3.4 mm agreed well with experimentation. Synergic effect of particle impaction and particle sticking systematically analysed. The effect of flue gas temperature overweighs that of particle or probe temperature. The role of Na in initiating deposition confirmed by considering particle chemistry. Abstract: In the present work, a modified critical viscosity model considering condensation, thermophoresis and inertia impaction has been established to simulate ash deposition on a probe perpendicularly placed in the flue path in a circulating fluidized bed (CFB) burning high-sodium (Na) Zhundong lignite (ZD). The key influencing factors including flue gas velocity (3 – 15 m/s) and temperature (1023 – 1123 K), probe surface temperature (773 – 873 K), particle temperature (1073 – 1173 K), particle size (5 – 127 µm), and particle chemistry were systematically simulated and also experimental observed. The simulation results show that the thickness of the deposit on the windward side reached 3.4 mm over 6 h, which agreed well with the experimental observation. The deposit incurred an increase in the surface temperature to 1000 K, reducing the heat flux by 62.5 %. The mean size of the deposited ash at the stagnant point was found to be 25 – 30 µm, signifying its role in the deposition initiation. This is attributed to the synergistic effect of particle impaction and particle sticking, since particles with a higher Stokes number (0 – 8) would have a higher impaction probability (0 – 0.3) but a lower sticking probability once their kinetic energy exceeds 11.4 × 10 -9 J. Moreover, ash deposition is also found to be affected by flue gas temperature, followed by particle temperature and probe temperature to a less degree. In addition, particles with smaller sizes rich in Na tended to deposit on the probe than those particles with larger sizes and abundant in Si and Al, highlighting the role of Na in initiating ash deposition during ZD CFB combustion.